Pengaruh Lingkungan kerja dan Komunikasi Terhadap Kepuasan Kerja Paramedis Rumah Sakit Bina Kasih Pekanbaru - Manalu, Eka Lestari; Hendriani, Susi; Ningsih, Dewita Suryati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The study to analyze the influence of Work Environment and communication on employee Job Satisfaction of medics. The population of this study was a;; medis of Bina Kasih Hospital {ekanbaru. The result of this indicate that the Work Environment has a significant effect on the job satisfactionof medics. Communication has a significant effect on the job satisfaction of medics. Work environment and communication positive effect on the job satisfactionof medics.Keywords : Work Environment, Communication, Job Satisfaction